Perlindungan Hukum Bagi Pihak Kreditur dalam Perjanjian Jaminan Fidusia - Siti Putri Nera Usmaina; Rani Apriani (Universitas Batanghari Jambi, 2022)
Weak legal protection for creditors in fiduciary guarantee agreements, even though guarantees have a very important role in economic activity in providing capital loans from financial institutions, both banks and non-banks in which there are long-term and short-term guarantees which are a form of protection. law in an agreement that can provide a sense of security, comfort for individuals. This study aims to determine legal protection for creditors in fiduciary guarantees in order to create legal certainty by using data collection methods based on laws which are normatively tested by applying existing values or rules given by law enforcement officials for the sake of the achievement of public order which includes elements of protective actions and ways of protecting. And the purpose of the methodology in this paper is to provide data about the situation which can later be analyzed in accordance with existing laws and regulations. For this reason, legal protection for creditors in a fiduciary agreement is born on the registration of the agreement deed. UUJF has tried to provide technical protection for creditors, but it is not implemented explicitly in its implementation system so that the protection is still considered weak because it is not balanced with firmness in the execution of fiduciary guarantees.